Export Structure and Growth : A Detailed Analysis for Argentina - Guerson, Alejandro; Parks, James; Parra Torrado, Monica (World Bank, Washington, DC, 2012)
This paper examines recent changes in the structure of Argentine exports and the implications for future growth. The authors find that the current export structure of Argentina is not conducive to future growth because it is dominated by low-productivity goods that tend to be exported by low-income countries. The productivity content of Argentine exports has increased recently although, as of 2004, these changes have been relatively minor. The authors identify products with characteristics similar to those currently exported by Argentina and which are more likely to foster growth because they would shift the structure of exports more the efficiency frontier. Those products include chemicals and primary products with some degree of value added, including partly processed meat, fish and grains. If economic growth is to be fostered by developing new export products and by increasing the value added of existing exports, there will be a need for sector-specific analysis to address possible market failures. The analysis should focus on issues such as the provision of public goods needed for production (including infrastructure, but also complex intangibles such as sector-specific legislation), possible impediments to effective coordination, sector-specific and economy wide externalities, or barriers to information. This last source of potential market failure is critical to a successful policy framework for exports and growth.